Living with vaccine-induced immune thrombocytopenia and thrombosis: a qualitative study - Paul Bennett (BMJ Open, 2023)
Objectives: To explore the experiences of people up to 18 months after being diagnosed with vaccine-induced immune thrombocytopenia and thrombosis (VITT). Design: A semistructured qualitative study, conducted via Zoom, of a cohort of people with VITT. Setting: Participants discussed their experiences of hospitalisation and following discharge. Participants: 14 individuals diagnosed with VITT, recruited via a Facebook support group and advertising on Twitter. Results: Thematic analysis identified challenges of obtaining medical care and diagnosis; fear of the severity of symptoms and unclear prognosis; and lack of family support due to isolation imposed by the COVID-19 pandemic. Once home, participants experienced continued significant symptoms; fear of recurrence; inadequate medical knowledge of their condition; and difficulties coping with residual physical disabilities and psychosocial losses. Also reported were feelings of isolation and abandonment due to lack of government support. Conclusions: This is a significantly challenged group of people, with multiple health, financial, social and psychological losses. These losses have been compounded by experiences of limited governmental and societal recognition of the problems they face.